2000
DOI: 10.1093/emboj/19.11.2525
|View full text |Cite
|
Sign up to set email alerts
|

Cytohesin-1 regulates beta-2 integrin-mediated adhesion through both ARF-GEF function and interaction with LFA-1

Abstract: Intracellular signaling pathways, which regulate the interactions of integrins with their ligands, affect a wide variety of biological functions. Here we provide evidence of how cytohesin-1, an integrin-binding protein and guanine-nucleotide exchange factor (GEF) for ARF GTPases, regulates cell adhesion. Mutational analyses of the b-2 cytoplasmic domain revealed that the adhesive function of LFA-1 depends on its interaction with cytohesin-1, unless the integrin is activated by exogenous divalent cations. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
131
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 55 publications
6
131
1
Order By: Relevance
“…We and others have shown that cytohesin-1 is a key regulator of leukocyte adhesion with which its interaction with the cytoplasmic tail of CD18 brings about increased avidity of LFA-1 (CD18/CD11a) for ICAM-1 (12,16,56). Cytohesin-1 binds to and regulates ␤ 2 integrins and this process is positively regulated by the binding of the PI3K metabolite, PtdIns-3,4,5-P 3 , to the cytohesin-1 pleckstrin homology domain (13,36).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that cytohesin-1 is a key regulator of leukocyte adhesion with which its interaction with the cytoplasmic tail of CD18 brings about increased avidity of LFA-1 (CD18/CD11a) for ICAM-1 (12,16,56). Cytohesin-1 binds to and regulates ␤ 2 integrins and this process is positively regulated by the binding of the PI3K metabolite, PtdIns-3,4,5-P 3 , to the cytohesin-1 pleckstrin homology domain (13,36).…”
Section: Discussionmentioning
confidence: 99%
“…Cytohesin-1 but not ARNO expression increases with granulocytic differentiation (10,20), suggesting a potential role of cytohesin-1 in the acquisition of a granulocytic phenotype. In lymphocytes, cytohesin-1 regulates cell adhesion via b-2 integrin activation (21,22). Furthermore, a number of reports have implicated ARNO/cytohesin-2 in cell migration (23), vesicle trafficking (24,25), and the outgrowth and branching of neurites (26,27).…”
mentioning
confidence: 99%
“…T he cytohesin family members are cytoplasmic signaling proteins that are thought to be involved in integrin signaling (1), actin cytoskeleton remodeling events (2,3), and vesicle transport. They belong to a class of highly homologous guanine nucleotide exchange factors (GEFs), the small ADP-ribosylation factor (ARF)-GEFs, which catalyze the exchange of GDP for GTP on ARFs.…”
mentioning
confidence: 99%
“…For example, cytohesin-1 is a positive effector of leukocyte function-associated antigen-1 (LFA-1)-mediated cell adhesion, whereas this activity has not been shown for cytohesin-2, also known as ADP-ribosylation factor nucleotide-binding site opener (ARNO) (7), or other small GEFs (1). In addition, cytohesin-1 is involved in T cell activation mediated by intercellular adhesion molecule 2 and in stimulation of T cell proliferation by IL-2 (13).…”
mentioning
confidence: 99%